Aspects of Land Take in the Metropolitan Area of Naples - Mazzeo, Giuseppe; Russo, Laura (TeMA - Journal of Land Use, Mobility and Environment, 2016)
Land take is a phenomenon of great concern nowadays because of the large number of its negative impacts regarding biological, economic and social balance. In Italy, the development of urban and other artificial land has been irreversibly transforming a non-renewable resource such as soil, regardless the almost constant population rate, with different speed depending of the region considered. The aim of this paper is to analyze the phenomenon in the metropolitan area of Naples, which is an area highly affected by territorial aggression of human matrix. The data used are both by the Institute for Environmental Protection and Research (ISPRA) Report 2015 on the usage of the land and by ISTAT relating to the resident population up to the 1st of January 2015 and the extension of land for agricultural use (Census 2010). The mathematical combination of this data creates a new indicator that can be referred to as “residual land”; this residual area is of great extension with many different characteristics and it could represent the area where the phenomenon of land take most occurs. The identification, measurement and analysis of “residual land” provide new insights on the evolution of land take and this new indicator can represent a critical element to work on to prevent future land transformation and protect natural and agricultural areas within the Italian context.